BIROKRASI DAN KEKUASAAN POLITIK (Kasus: Partisipasi Birokrat dalam Pemilihan Kepala Daerah) - Basir, Gusril (Alhurriyah, 2009)
The strong desire of officials’ government to dominate a political power is not only caused by the strong restriction of government toward their political aspiration. But also this is involved by such factors like some desires to increase their income and their career performance, reaching up their prestige, even gaining a popularity. Unfortunately, we could not deny if they were snatching away to compete in the election of a district head. The government must be taking a part to create a clear rule related with this case. The government should criticize to whom breaking the rules decided without any specification. So that, the pros and cons about their participation could be minimize in the election of a district head and the society could accept the problem for this case.